Les déterminants de la trajectoire économique d'une pêcherie complexe : cas de la pêche française dans le golfe de Gascogne - Steinmetz, Fabien (Université de Bretagne Occidentale, 2010)
The average trophic level of the landings of the species landed by the french fleets in the Bay of Biscay is dropping since 30 years, according to the worldwide range observations of Daniel Pauly. The effects of the ecosystemic, institutional and economic factors of this drop are studied with two complementary approaches, a time series analysis and the interpretation of the phenomenons thanks to a bio-economic model. The major factors which could interact with the exploitation from 1973 to nowadays have been analysed. The short term study of the productions and the productivity of tree large trawler fleets from south brittany showed that they adapted according to their specificities to the constraints enforced by the stocks or the prices. At the larger case of the aggregated landings coming from the maritime area of the Bay of Biscay or the North-East Atlantic, we put in a obvious place the links between the evolution of the landing’s structure and of the biologic or economic factors, revealing particularly the rise of the pelagic landings. We observe that there is a relation between the price of imports and french landings prices, this link depending on the kind of fish market studied. A bio-economic model, based on the Gordon-Schaefer hypothesis enlarged to a predator-prey or competition system, shows the long term effects produced by the changes of technical progress, the regulation mode and the equilibrium price on the landings structure, some of these changes explaining the structural change of the landings observed in the Bay. Le niveau trophique moyen des espèces débarquées par les flottilles françaises du Golfe de Gascogne a baissé depuis 30 ans suivant en cela les observations de Daniel Pauly au niveau mondial. Les effets des déterminants écosystémiques, institutionnels et économiques de cette baisse sont étudiés par deux approches complémentaires d’analyse de séries temporelles et d’interprétation des phénomènes grâce à un modèle bio-économique. Les grands facteurs susceptibles d’interagir avec ...